Survey of Psoriasis Patient Awareness of Metabolic Syndrome Co-Morbidities. Issue 4 (December 2013) - Adelzadeh, Lily; Vangala, Sitaram; Chiu, Melvin W.
Background: Psoriasis patients are thought to be at increased risk of having metabolic syndrome. Objective: To investigate if psoriasis patients are aware of their condition's association with metabolic syndrome, and whether they have been educated about and screened for metabolic syndrome by their dermatologists. Methods: Written surveys distributed to psoriasis patients at a National Psoriasis Foundation fundraising event. Results: Of 49 patients who completed the survey, 16 (32.7%), 17 (34.7%), 16 (32.7%), 20 (40.8%), and 16 (32.7%) were aware of the link between psoriasis and diabetes, hypertension, dyslipidemia, obesity, and myocardial infarction, respectively. Only 4.7% to 32.6% of the respondents reported being educated about the link between psoriasis and metabolic syndrome, and 19.6% to 39.1% reported having been screened by their dermatologist for metabolic syndrome components. Limitations: Patients may not remember or be aware they are being taught or screened for metabolic syndrome. Conclusion: The majority of psoriasis patients in this survey were unaware of the association of psoriasis with metabolic syndrome and reported infrequent teaching and screening by their dermatologists.